Preparation of core-shell structure KClO4@Al/CuO Nanoenergetic material and enhancement of thermal behavior - Fan Yang (Nature Portfolio, 2017)
Abstract In this paper, a solvent/non-solvent synthetic approach has been utilized in preparing a new nanoenergetic material KClO4@Al/CuO by coating Al/CuO nanocomposites particles with a layer of nanoscale oxidizer KClO4. The coating process and mechanism are discussed. The composites of Al/CuO are uniformly mixed by mechanical ball milling process and CuO acts as a catalytic metallic oxide. The ternary mixtures KClO4@Al/CuO were characterized by X-ray diffraction (XRD) and the results reveal that after ball-milling and chemical synthesis process, the phase compositions haven’t changed. Scan electron microscopy (SEM) images show that these energetic nanocomposites consist of small clusters of Al/CuO that are in intimate contact with a continuous and clear-cut KClO4 layer (100–400 nm). In a Scanning transmission electron microscopy (STEM) elemental map, high K/Cl intensity on the perimeter of the nanoparticles and high Cu/Al content in the interior powerfully demonstrated the KClO4@Al/CuO core-shell nanostructure. Electrical ignition experiments and pressure cell test prove that these nanoenergetic composites are more sensitive to ignition with much higher burning rate than traditional formulations (conventional counterparts). To quantify the enhancement of thermal behavior, Thermogravimetry (TG) and Differential scanning calorimetry (DSC) were performed and the results show that the burning rate of these energetic nanocomposites nearly tripled.